2019
DOI: 10.1126/science.aav6335
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of ruminant headgear and rapid antler regeneration

Abstract: Ruminants are the only extant mammalian group possessing bony (osseous) headgear. We obtained 221 transcriptomes from bovids and cervids and sequenced three genomes representing the only two pecoran lineages that convergently lack headgear. Comparative analyses reveal that bovid horns and cervid antlers share similar gene expression profiles and a common cellular basis developed from neural crest stem cells. The rapid regenerative properties of antler tissue involve exploitation of oncogenetic pathways, and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
156
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 142 publications
(165 citation statements)
references
References 82 publications
9
156
0
Order By: Relevance
“…This study identified 624 horn‐specific genes using transcriptomes from 16 tissues, including horn sprouts from goats and sheep, and fetal horn bud and frontal skin from sheep (Wang et al ), but no other candidate genes (Table ) were found to be horn‐specific. FOXC2 is highly expressed in horn tissue and bone (Wang et al ). FOXC2 was also found to be differentially expressed between the horn bud and frontal skin of horned (p/p) bovine fetuses at 90 days of development (Allais‐Bonnet et al ).…”
Section: Candidate Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…This study identified 624 horn‐specific genes using transcriptomes from 16 tissues, including horn sprouts from goats and sheep, and fetal horn bud and frontal skin from sheep (Wang et al ), but no other candidate genes (Table ) were found to be horn‐specific. FOXC2 is highly expressed in horn tissue and bone (Wang et al ). FOXC2 was also found to be differentially expressed between the horn bud and frontal skin of horned (p/p) bovine fetuses at 90 days of development (Allais‐Bonnet et al ).…”
Section: Candidate Genesmentioning
confidence: 99%
“…The cranial neural crest cells migrate to form the frontal and facial bones (Wu et al ), and these cells are the most likely candidates to form horns in Bovidae species. In an immunohistochemistry study of sheep fetuses, cells expressing genetic markers for neural crest cells (SOX10 and NFGR) were found in the fetal horn bud at 90 days of development (Wang et al ).…”
Section: Candidate Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…We sequenced transcriptomes of 33 samples across 14 adult tissues from Bactrian camels, eight adult tissues from one species in Mysticeti (Bryde’s whale) and one species in Odontoceti (Indo-Pacific Finless Porpoise) from Cetacea, 852 samples (210 sequenced in this study and 642 published in previous studies 7,18,19 ) from 50 tissues of two representative ruminants (sheep and roe deer) within Ruminantia ( Supplementary Table 1 ). The global gene expression patterns of all the FC stomachs are consistently most similar to the esophagus in all species (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The origin of some notable organs has been central to animal evolution, e.g. the eyes of animals 2,3 , electric organs of fishes 4 , mammalian placenta 5,6 and ruminant headgear 7 . Another remarkable organ innovation found in mammals are the multi-chambered stomachs found in the Cetartiodactyla lineages, including Tylopoda (e.g.…”
Section: Figmentioning
confidence: 99%